PERBEDAAN ANTARA TINGKAT KEMANDIRIAN PERSONAL HYGIENE PADA ANAK USIA 6-12 TAHUN SEBELUM DAN SESUDAH DIBERIKAN PROMOSI KESEHATAN DI PANTI ASUHAN MUHAMMADIYAH KOTA DUMAI - Puspaini, Ririn (Jurnal Martenity and Neonatal, 2019)
Personal hygiene is an effort made by individuals in maintaining their hygiene and health both physically and mentally. Being clean, fragrant, and neat is a very important dimension in measuring the level of individual welfare in general. The purpose of this study to determine the difference between the level of independence of personal hygiene in children aged 6-12 years before and after being given health promotion at the orphanage muhammadiyah kota dumai The research design is quasi experimental research with time series design approach with 10 samples. The results of this study there is a significant difference between mean independence of children before and after health promotion (p = 0,000). It is recommended for muhammadiyah kota dumai City to be able to use the results of this research as information to improve the independence of children in taking care of themselves.